Pengaruh social support dengan peer leader untuk meningkatkan self management diabetic pada sesama penderita DM tipe II di Posyandu Lansia - Khairani, Wittin; Purwanti, Nunuk Sri (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
ABSTRACTThe phenomenon of cases of diabetes mellitus from year to year continues to increase. According to the International Diabetes Federation (2019) revealed that the number of diabetes mellitus patients in the world in 2019 was 829 million and it is estimated that in 2040 the number of diabetes patients will increase 1.5 times. The prevalence of diabetes mellitus in the Special Region of Yogyakarta continues to increase every year. The prevalence of Diabetes Mellitus in DI Yogyakarta Province, in 2020, is 5.59 percent. This figure has even increased compared to the results of research seven years earlier in 2013, namely 3.4 percent.To determine the effect and differences in increasing diabetic self-management before and after intervention through social support with peer leaders among people with type II DM in the elderly Posyandu.This research used a quasi-experimental design with a pre-test and post-test nonequivalent control group design. The study population was all type II diabetes sufferers at the Elderly Posyandu in Ngentak, Bangunjiwo, Kasihan, Bantul, DI Yogyakarta from September 2022 to June 2023 with a sample size of 50 respondents using purposive sampling. The data collection instrument used a respondent characteristic questionnaire, and a diabetes self management knowledge questionnaire. Data were analyzed univariately and bivariately with q-square test (95% CI). In this design, the experimental group underwent an initial selection in the form of a pre-test, namely the assessment of diabetic self-management in type II DM patients before the social support intervention with peer leaders was carried out, then a post-test was carried out after the intervention was given.There is an effect of increasing diabetic self-management knowledge, seen from the difference in the mean value from pretest to posttest of only 10,5 in the respondents' answers. There was a difference from the pretest to the posttest scores, seen from the significance of p = 0.000 (p <0.05) after being given interventions about social support with peer leaders among people with type II DM in the elderly Posyandu.There are influences and differences in the form of increasing diabetic self-management after being given intervention to fellow DM type II sufferers at the Elderly Posyandu in Ngentak hamlet, Bangunjiwo, DI Yogyakarta Keywords: Diabetic self management, social support, peer leader, type II diabetic